THE ROLE OF SHARIAH SUPERVISORY BOARD IN ISLAMIC FINANCIAL INDUSTRY - Arsyianti, Laily Dwi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2010)
The obligatory of indoctrinating Muslim society with Islamic norm is unequivocally a need itself. Since the demand and the progress of Islamic financial industry has been growth immensely, an independent body auditing the operation becomes indispensable from day to day. It is not only auditing for the accountability of the Islamic financial institution (IFI)’s operation but also an auditing for the operation to be Shariah compliance. The Shariah supervisory board (SSB), comprises high caliber scholars, is formed in order to assess whether the operations and the products offered by IFIs are complying Shariah rules, in general. This paper elaborates their responsibilities and the manner of SSB in conducting their role in order to achieve the good corporate governance. Since the methodology usedby scholars in their interpretation may differ and the circumstances faced when drawing conclusions and interpretation may also differ, different resolution may actually arise among them. Hence, it may difficult to achieve consensus in every issue, not only among scholars but also among Shariah forums. This paper also discusses and compares the different structure applied by Iran, Indonesia, and Malaysia financial systems.